Credible Voice of Sofyan Tsauri as The Deradicalization Strategy for Former Terrorism Prisoners - Nasution, Solihuddin; Sukabdi, Zora; Priyanto, Sapto (Technium Social Sciences Journal, 2021)
Countering terrorism should be a priority in Indonesia, because there are many terrorism cases from The Old Order Era to present. The government takes hard and soft approaches to overcome the terrorism, by arrested the terrorist, convictions, and guidance and also empowerment programs. However, terrorism has not been resolved, because there are several former terrorism prisoners re-join their terror movement. To disengage former terrorism prisoners with their networks, we need de-radicalization programs through social learning as Sofyan Tsauri do. The social learning is applied by voicing his experience so it can lead the people who want to join the radical organization and former terrorism prisoners far from radicalism. This research uses qualitative method by conducting unstructured interviews and also use some literature studies as secondary data. From this qualitative method, it is aimed to get the deep understanding about the ideology of terrorism, the experience, and the dialogue with former terrorism prisoners to get the effective strategies for countering the terrorism.